PENGEMBANGAN BADAN USAHA MILIK DESA BERBASIS PARTISIPATIF DI KABUPATEN BREBES - Aswhar Anis (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2020)
The rural economic organization is an important part as well as a weak point in supporting the strengthening of the rural economy. Therefore, a systematic effort is needed to encourage this organization to be able to manage strategic economic assets in the village and at the same time develop economic networks in order to increase the competitiveness of the rural economy. In this context, BUMDes is basically a form of consolidation or strengthening of village economic institutions. The development of a very large potential for the regional government of Brebes Regency to increase economic growth and regional development, through the BUMDes opportunity to mobilize development and become an economic driver in the village.Key Words: public policy, bumdes, village, participation